Parental and predatory behaviour of scytodes sp., an araneophagic spitting spider (araneae : scytodidae) from the philippines - Li, Daiqin; Jackson, Robert R.; Barrion, Alberto T. (Wiley, 1999)
Parental care, especially as it relates to our understanding of sociality, is a topic that has received considerable recent attention in research on spiders (Aviles, 1997). Predatory strategies, including foraging decisions, prey preferences and predatory versatility, have also been emphasized in the recent literature. The present paper is concerned with both of these areas, parental care and predatory strategies. Scytodes sp. indet. is a versatile predator that captures prey either in its web or away from webs, and prey capture may be either by ambush or by active pursuit regardless of whether in the presence and absence of webs. The web is a sparsely woven sheet across a concave upper leaf surface, with a three‐dimensional tubular nest linked to the sheet via a small opening. Leaves may be green and living or brown and dead. In the field, a wide range of insects and spiders is taken, but jumping spiders (Salticidae) are the dominant prey. Predatory attacks are by spitting, with large prey being spat at repeatedly before being subdued. After spitting, the scytodid wraps prey in silk before feeding. Eggs are enclosed in a silk egg sac. The female uses her chelicerae to hold her eggs until hatching. After hatching, there is an extended mother–offspring association, with juveniles tending to remain in their mother's web until after the third moult. Females take prey to their juveniles and either feed alongside the juveniles or leave the juveniles to feed alone.